Exploring Factors Affecting Millennial Tourists’ eWOM Behavior: A Lens of BRT Theory - Zibin Song; Yingying Ren; Jie Li (Behavioral Sciences)
This study employs behavioral reasoning theory (BRT) to investigate factors (i.e., personal values, reasons, and attitudes) affecting existing and future behaviors of Millennial tourists’ electronic word-of-mouth (eWOM). It uses a mixed-methods approach that includes qualitative interviews with 25 tourists to elicit specific reasons for and against eWOM and a survey of 572 Millennial-Chinese tourists to quantitatively validate our BRT structural model. The statistical results from SmartPLS 3.0 show that all hypotheses on direct effects have gained empirical support except for the relationships between the existing behavior and its respective reasons for and against eWOM. These two insignificant direct effects are, however, shown to be fully mediated by global attitudes, respectively. Moreover, gender moderates the relationships between reasons against eWOM and the existing behavior and reasons for eWOM and future behavior, respectively. Most findings regarding the foregoing direct, mediation, and moderation effects are exploratory. In addition, this study contributes significantly to the literature by successfully developing and validating the scale of reasons for and against Millennial tourists’ eWOM within the BRT framework. Destination managers can use this scale of reasons as both a diagnostic tool and a blueprint for eWOM management.